Interventions in the B‐type natriuretic peptide signalling pathway as a means of controlling chronic itch. (12th February 2020) - Meng, Jianghui; Chen, Weiwei; Wang, Jiafu
Abstract : Chronic itch poses major health care and economic burdens worldwide. In 2013, B‐type natriuretic peptide (BNP) was identified as an itch‐selective neuropeptide and shown to be both necessary and sufficient to produce itch behaviour in mice. Since then, mechanistic studies of itch have increased, not only at central levels of the spinal relay of itch signalling but also in the periphery and skin. In this review, we have critically analysed recent findings from complementary pharmacological and physiological approaches, combined with genetic strategies to examine the role of BNP in itch transduction and modulation of other pruritic proteins. Additionally, potential targets and possible strategies against BNP signalling are discussed for developing novel therapeutics in itch. Overall, we aim to provide insights into drug development by altering BNP signalling to modulate disease symptoms in chronic itch, including conditions for which no approved treatment exists.